2015
DOI: 10.1242/dev.117341
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt1 is essential to maintain progenitors in the perinatal intestinal epithelium

Abstract: The DNA methyltransferase Dnmt1 maintains DNA methylation patterns and genomic stability in several in vitro cell systems. Ablation of Dnmt1 in mouse embryos causes death at the postgastrulation stage; however, the functions of Dnmt1 and DNA methylation in organogenesis remain unclear. Here, we report that Dnmt1 is crucial during perinatal intestinal development. Loss of Dnmt1 in intervillus progenitor cells causes global hypomethylation, DNA damage, premature differentiation, apoptosis and, consequently, loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…Recently, Kang et al (2015) also reported that Tet1-deficient C57BL/6 mice exhibit partial embryonic lethality and growth retardation; however, intestinal health was not examined in the prior study. Tet1 −/− mice exhibited shortened intestinal length and reduced proliferating cell number in the postnatal intestine, which is similar to the phenotype seen in mice with conditional deletion of Dnmt1 in the developing gut using Dnmt1 f/f ; VillinCre mice (Elliott et al 2015;Yu et al 2015).…”
Section: Discussionsupporting
confidence: 65%
“…Recently, Kang et al (2015) also reported that Tet1-deficient C57BL/6 mice exhibit partial embryonic lethality and growth retardation; however, intestinal health was not examined in the prior study. Tet1 −/− mice exhibited shortened intestinal length and reduced proliferating cell number in the postnatal intestine, which is similar to the phenotype seen in mice with conditional deletion of Dnmt1 in the developing gut using Dnmt1 f/f ; VillinCre mice (Elliott et al 2015;Yu et al 2015).…”
Section: Discussionsupporting
confidence: 65%
“…Genome-wide examination of the postnatal methylome revealed microbiota-dependent increases in DNA methylation in intestinal stem cells within maturation-associated genes that positively correlated with increased gene expression [76]. IEC-specific deletion of the methyltransferase Dnmt1 resulted in global DNA hypomethylation, aberrant crypt formation and stunted colonic development [76,77]. While SCFAs and the epigenome have not been studied in vivo to the same extent as immune cells, recent work has demonstrated previously unrecognized differential effects of butyrate on differentiated versus stem cell IECs (Fig.…”
Section: Epigenomic Pathways Directed By the Microbiota Maintain Intementioning
confidence: 99%
“…Importantly, cytosine methylation (5-mc) is preserved during mitosis through DNA methyltransferase 1 (DNMT), which recognizes hemi-methylated DNA during the S-phase of mitosis and copies this patern to the daughter strand [13][14][15]. This mechanism is essential to maintain tissue homogeneity and cell lineage in terminally diferentiated cells, and there are many publications that have established DNA methylation proiles speciic to certain tissues and additionally tissues or cells with similar functions have similar methylation proiles [16,17].…”
Section: Dna Methylationmentioning
confidence: 99%